Latin American imperialism and structural dependence: Some conceptual, historical and contemporary aspects - da Silva, Luiz Fernando [UNESP] (My University, 2020)
This article discusses Latin American structural dependence. At least since the 1920s, this theme has enabled an axis of interpretations on social misery and economic retardment in the region. The main emphasis for this explanation was found in the subordination relations to the imperialist countries in alliance with the local national bourgeoisies. The topic today is rarely addressed in academic circles and even by a large part of the political left. The globalization did not eliminate the process of structural dependency but empowered it. It is not possible to consider such a phenomenon without also considering the so-called progressive governments, which developed in South America, starting in the late 1990s. The new forms of extractivism that expanded over huge territorial areas, with the sign of the mega mining and agricultural enterprises of international groups on the original peoples, peasants and quilombolas, gained new expansion in progressive governments. In this current period, the new right-wing and ultra-right governments are working to further deepen this dependency.
Imperialismo e dependência estrutural Latino-Americana: Alguns aspectos conceituais, históricos e contemporâneos
Keywords: Imperialism; Latin America and the Caribbean; Social thought; Structural dependence